A faster algorithm for the resource allocation problem with convex cost functions - Shi, Cong; Zhang, Huanan; Qin, Chao (Journal of discrete algorithms (Amsterdam, Netherlands), 2015)
We revisit the classical resource allocation problem with general convex objective functions, subject to an integer knapsack constraint. This class of problems is fundamental in discrete optimization and arises in a wide variety of applications. In this paper, we propose a novel polynomial-time divide-and-conquer algorithm (called the multi-phase algorithm) and prove that it has a computational complexity of O(nlog⁡nlog⁡N), which outperforms the best known polynomial-time algorithm with O(n(log⁡N)2).